A Convenient and Practical Synthesis of Aminopyrazoles - Mitchell, David; Luo, Yumei; McNulty, Lu Anne M.; Buser, Jonas Y.; McFarland, Adam D. (Synthesis, 2015)
A selective methodology for preparing highly substituted aminopyrazoles has been demonstrated. Starting with an acetophenol core, the corresponding substituted isoxazole is prepared in two steps. The isoxazole is transformed into a benzopyran. Alkylation of the aminobenzopyranone gives N-substituted aminobenzopyranone derivatives that react with substituted hydrazine to give aminopyrazoles. This versatile synthesis enables the preparation of highly substituted aminopyrazoles for use as key synthetic building blocks for biologically active molecules. In addition, this process represents the first amine alkylation of aminobenzopyranones.
Keywords: aminopyrazoles; selectivity; isoxazoles; benzopyran; heterocycles